Alexandre de Humboldt et Aimé Bonpland, botanistes de l’Amérique hispanique (1799-1804) : de la taxonomie à l’épistémologie - Michèle Guicharnaud-Tollis (Caravelle)
An absolute Eldorado for botanical travelers, Spanish-American equinoctial lands were for A. de Humboldt and A. Bonpland a wide space practically unexplored, full of sensations, observations and experiments in specific scientific areas that often went beyond simple botany. This article shows how the newly discovered plants’ representation integrates for Humboldt into a system of thoughts about Nature, inherited from his own times. Well beyond, this reinforced intuitions previously only glimpsed: the making of herbariums led to theories about plants’ geography (1805) and novel epystemological reflections about their « metamorphosis » and integration inside a living and evolving Cosmos.